Contraceptive use and counselling in women with mental illness: KwaZulu-Natal, South Africa - Lisa Peralta; Reyanta Bridgmohun; Thandokazi Mcizana (South African Journal of Psychiatry, 2025)
Background: While women with mental illness are prone to unplanned pregnancies, sexual violence and exposure to teratogenic medications, there is limited knowledge of contraceptive use and counselling in this vulnerable group.